2014
DOI: 10.1136/bmjopen-2014-005351
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of HIV and syphilis among migrant men who have sex with men in Beijing, China: a prospective cohort study

Abstract: ObjectivesThe purpose of the study was to investigate the incidence of HIV and syphilis and their related factors, as well as to examine the predictors associated with seroconversion among migrant men who have sex with men (MSM) in Beijing, China.DesignProspective cohort study.SettingBeijing, China.Participants511 HIV-negative migrant MSM.Primary and secondary outcome measuresSociodemographic and behavioural information of participants, HIV and syphilis incidence rates, and factors associated with HIV/syphilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 24 publications
8
38
4
Order By: Relevance
“…Migrant MSM are less empowered at the place of destination in comparison to their non-migrant counterpart, which may be reason behind low prevalence of condom use in case of sex with females. A similar finding was observed in a study in China, where major reasons for such a finding could be that migrants MSM, who had sex with females, may have more varied sexual behaviors with a wider range of sexual partners among both males and females [13]. Further, a cross-sectional study among migrant MSM in Beijing revealed that MSM who were involved in bisexual behavior had a higher proportion of unsafe sex with stable female partners and were less likely to take a part in preventive behaviors [14].…”
Section: Discussionsupporting
confidence: 69%
“…Migrant MSM are less empowered at the place of destination in comparison to their non-migrant counterpart, which may be reason behind low prevalence of condom use in case of sex with females. A similar finding was observed in a study in China, where major reasons for such a finding could be that migrants MSM, who had sex with females, may have more varied sexual behaviors with a wider range of sexual partners among both males and females [13]. Further, a cross-sectional study among migrant MSM in Beijing revealed that MSM who were involved in bisexual behavior had a higher proportion of unsafe sex with stable female partners and were less likely to take a part in preventive behaviors [14].…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, the MSM in our study living in Beijing for fewer years or without Beijing 'Hukou' were more likely to frequent non- † Includes: beach, woods, street, theater, public transportation, hotel and private homes Internet venues. This subgroup might include a majority of transient workers (migrants) from village/township/country level cities to large cities for better employment opportunities and living condition [44,45]. These marginal population might be less educated and faced financial constraints [44], both barriers to the conduct of online sexfinding.…”
Section: Discussionmentioning
confidence: 98%
“…Large numbers of single men increase the possibility of HIV spread due to male-male sexual activity or sexual contact with sex workers. 52 …”
Section: Discussionmentioning
confidence: 99%